Reading the human body : physiognomics and astrology in the Dead Sea scrolls and Hellenistic-early Roman period Judaism - Popović, Mladen. (Studies on the texts of the desert of Judah,, 2007)
This study deals with physiognomic and astrological texts from the Dead Sea Scrolls that represent one of the earliest examples of ancient Jewish science. For the first time the Hebrew physiognomic-astrological list 4Q186 (4QZodiacal Physiognomy) and the Aramaic physiognomic list 4Q561 (4QPhysiognomy ar) are comprehensively studied in relation to both physiognomic and astrological writings from Babylonian and Greco-Roman traditions. New reconstructions and interpretations of these learned lists are offered that result in a fresh view of their sense, function, and status within both the Qumran community and Second Temple Judaism at large, showing that Jewish culture in Palestine participated in the cultural exchange of learned knowledge between Babylonian and Greco-Roman cultures.